2022
DOI: 10.2478/aoas-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Use of Distillers Dried Grains with Solubles (DDGS) in Aquaculture Feeds

Abstract: Distiller’s dried grains with soluble (DDGS) to replace fishmeal (FM) or other plant protein sources and its effects on an aquatic animal’s growth performance and health system is rarely discussed. In recent times FM use in aquafeed has been a problem for the aquaculture industry because of the depletion of fish resources in the ocean and the high cost of FM. For that reason, researchers are focusing on reducing the cost of aquafeed production by lowering the inclusion of FM in aquafeed. One of the low-cost al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…Stein and Shurson (2009) observed that the fiber content in maize is not converted to ethanol, increasing the fiber content in DDGS that is approximately an insoluble fiber of 35% and a soluble fiber of 6% than in FM (Stein and Shurson 2009). The apparent total tract digestibility of fiber in FM is less than that of DDGS: 43.7% (Ray et al 2022). These nutrients help to confer increased energy in shrimp, which further improves growth performance when included in shrimp diets (Stein et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stein and Shurson (2009) observed that the fiber content in maize is not converted to ethanol, increasing the fiber content in DDGS that is approximately an insoluble fiber of 35% and a soluble fiber of 6% than in FM (Stein and Shurson 2009). The apparent total tract digestibility of fiber in FM is less than that of DDGS: 43.7% (Ray et al 2022). These nutrients help to confer increased energy in shrimp, which further improves growth performance when included in shrimp diets (Stein et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Distillers’ dried grains with solubles are among the best underutilized by‐products from the alcohol industry and can used as a substitute for FM in a shrimp feed. Except for the fiber content, DDGS do not contain the anti‐nutritional factors that are found in most PP sources, such as SBM and peanut meal (Gyan et al 2021; Ray et al 2022). Bhadra et al (2007) stated that the chemical composition and qualities of DDGS could change depending on the ethanol plant used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These high‐protein distillers grains with yeast were manufactured to have decreased levels of fiber and higher protein content, allowing for the inclusion of these ingredients at higher levels in practical shrimp feeds without instigating negative effects on the digestive physiology of shrimp as the addition of more insoluble fiber in shrimp diets would decrease the digestibility of other dietary components, such as gross energy, dry matter, amino acids, and minerals (Ray et al. 2022). Moreover, methionine, lysine, and arginine are considered to be the most limiting essential amino acids in feed formulations for Pacific white shrimp (Akiyama et al.…”
Section: Discussionmentioning
confidence: 99%
“…Production from fisheries and aquaculture has significantly increased globally over the past few decades (Ray et al, 2020(Ray et al, , 2022Gyan et al, 2021). By 2030, the world will require an additional 23 million tons of aquatic food to maintain current per capita fish consumption due to the predicted increase in the human population .…”
mentioning
confidence: 99%